Extramedullary plasmacytoma of the tongue base: A rare presentation of head and neck plasmacytoma - Bila, Jelena Sreten; Andjelić, Boško; Bodrožić, Jelena; Jaković, Ljubomir; Peruničić Jovanović, Maja; Vidović, Ana; Todorović, Milena; Biljana, Mihaljević (Vojnosanitetski pregled, 2017)
Introduction. Special entities like solitary bone plasmocytoma (SBP) or extramedullary plasmacytoma (EMP) can be found in a less than 5% of patients with plasma cell disorders. EMP of the tongue represents very rare localization of the head and neck plasmacytoma. Case report. We report a case of 78-years-old woman who developed EMP of the tongue base detected by the magnetic resonance imaging (MRI) of the head and neck region. Immunohistochemical profile of the tumor tissue biopsy (CD38, IgG, kappa positivity) indicated diagnosis of EMP. The diagnosis was established with additional staging which confirmed the absence of other manifestation of the disease. The patient was treated with 40 Gy of radiotherapy in 20 doses resulting in the achievement of the complete remission of the disease. This case was discussed with the reference to the literature. Conclusion. EMP of the tongue base is a very rare entity of plasma cell dyscrasias. Appropriate irradiation results in the achievement of a long-term remission and a potential cure of the disease.
Keywords: plasmacytoma; diagnosis; tongue; radiotherapy; treatment outcome